2002
DOI: 10.1002/kin.10109
|View full text |Cite
|
Sign up to set email alerts
|

Relative rate constants for the reactions of hydroxyl radicals and chlorine atoms with a series of aliphatic alcohols

Abstract: Rate constants for the gas-phase reactions of hydroxyl radicals and chlorine atoms with a series of alcohols have been determined by using the relative method. The experiments were performed at 295 ± 2 K and at 1 atmospheric pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 26 publications
13
50
0
Order By: Relevance
“…As seen in Table 1, our result agrees well with the previous values obtained in absolute methods [18][19][20][21][22] and the result obtained by Wu et al [23] by similar technique. We could believe that our smog chamber system is suitable for the simulation of gas phase reactions of OH radicals with VOC.…”
Section: Kinetics Of Oh Radicals With Ethanolsupporting
confidence: 93%
“…As seen in Table 1, our result agrees well with the previous values obtained in absolute methods [18][19][20][21][22] and the result obtained by Wu et al [23] by similar technique. We could believe that our smog chamber system is suitable for the simulation of gas phase reactions of OH radicals with VOC.…”
Section: Kinetics Of Oh Radicals With Ethanolsupporting
confidence: 93%
“…[1][2][3][4][5][6] In addition, both ethanol and OH have been detected in interstellar molecular clouds and star forming regions (hot and cold cores) such as W3(OH) and Sgr B2, where temperatures can reach as low as 40 K. [7][8][9][10][11][12][13] Millar et al 12 suggested that ethanol could potentially be used as a chemical clock for hot cores if the kinetics of its reactions with species including the hydroxyl radical were better understood at temperatures pertinent to such environments. Conducting kinetic studies with species known to be present in these cold environments is important for the advancement of chemical models of these regions.…”
Section: Introductionmentioning
confidence: 99%
“…The rate constants for the reaction of OH radicals with H 2 S were calculated using the value of k (OH+propane) =1. [19] according to eq. (4), and the results are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic experiments were carried out in a previously described system [19,20], which was modified by replacing the cubic ligneous chamber to a thermostatic chamber (1. A gas chromatograph (GC-6AM, Shimadzu, Japan) equipped with a flame photometer detector (FPD) was used for quantitative analysis of H 2 S. H 2 S in the reaction mixtures was separated on a 3 m × 4 mm glass column packed with 20% SE 30 on Chromosorb P (60-80 mesh).…”
Section: Methodsmentioning
confidence: 99%